Blood Pressure and Arterial Wall Mechanics in Cardiovascular Diseases - Safar, Michel E.; O'Rourke, Michael F.; Frohlich, Edward D. (Springer London : Imprint: Springer, 2014)
In cardiovascular prevention, there has traditionally been a small number of cardiovascular risk factors to evaluate and manage, such as hypertension, diabetes, hyperlipidemia and smoking. Recently, it has been recognized that new mechanical factors should be identified, and specifically involves pulsatile arterial hemodynamic parameters, such as arterial stiffness, pulse pressure and, to a lesser extent, augmentation index and pulse pressure amplification.   Blood Pressure and Arterial Wall Mechanics in Cardiovascular Diseases has been written to facilitate understanding of these new concepts regarding bleed pressure and cardiac risk, and prepare the reader for the considerable evolution of the topic in the years to come. Much has been learned already regarding the management of these patients, and this book presents extensive data on the techniques needed to maximize their outcomes.